As if it were a poem: something about A casa do diabo, by Mafalda Ivo Cruz - Maffei, Luis (ITINERÁRIOS – Revue de Littérature, 2008)
Only a few examples of the contemporary novel get as close to poetry’s particular diction as A casa do diabo, by Mafalda Ivo Cruz. It is undoubtedly a work of prose, a narrative. However, the senses meet, in the novel, in a state of such “multisignification” that they end up making this work a hybrid example, not only capable of stories (for instance, the fortunes and misfortunes of a woman, the protagonist, a mother, a lover, who has no place in a unpropitious scene) but also of a lyricism always ready to allow the words to escape from their conventional meaning. Besides that, the presence of music in the novel is remarkable, which gives it another means of escape from the solid meanings of current speech, and also to what is conventionally expected from a novel.